Preclinical models for bladder cancer therapy research - Ertl, Iris; Shariat, Shahrokh F; Berger, Walter; Englinger, Bernard (Current opinion in urology, 2024)
PURPOSE OF REVIEW: Bladder cancer (BC) is a highly heterogenous disease comprising tumours of various molecular subtypes and histologic variants. This heterogeneity represents a major challenge for the development of novel therapeutics. Preclinical models that closely mimic in vivo tumours and reflect their diverse biology are indispensable for the identification of therapies with specific activity in various BC subtypes. In this review, we summarize efforts and progress made in this context during the last 24 months. RECENT FINDINGS: In recent years, one main focus was laid on the development of patient-derived BC models. Patient-derived organoids (PDOs) and patient-derived xenografts (PDXs) were demonstrated to widely recapitulate the molecular and histopathological characteristics, as well as the drug response profiles of the corresponding tumours of origin. These models, thus, represent promising tools for drug development and personalized medicine. Besides PDXs, syngenic in vivo models are of growing importance. Since these models are generated using immunocompetent hosts, they can, amongst others, be used to develop novel immunotherapeutics and to evaluate the impact of the immune system on drug response and resistance. SUMMARY: In the past two years, various in vivo and in vitro models closely recapitulating the biology and heterogeneity of human bladder tumours were developed.
Keywords: protinádorové látky; organoidy; Xenograft Model Antitumor Assays; xenogenní modely - testy protinádorové aktivity; Antineoplastic Agents; Animals; Humans; lidé; nádory močového měchýře; individualizovaná medicína; zvířata; Urinary Bladder Neoplasms; Disease Models, Animal; Precision Medicine; modely nemocí na zvířatech; Organoids